The effect of an acute antioxidant supplementation compared with placebo on performance and hormonal response during a high volume resistance training session - Ackerman, J.; Clifford, T.; McNaughton, L. R.; Bentley, D. J. (Journal of the International Society of Sports Nutrition, 2014)
Antioxidant supplementation is known to increase human endogenous antioxidant (AOX) capacity providing a means of blunting exercise induced reactive oxygen species (ROS). The purpose of this study was to compare the effects of a single acute dose of an AOX (vs blinded placebo) on muscle contractile performance and hormonal responses to a single bout of lower limb `hypertrophic` resistance training (RT). Fifteen resistance trained subjects (age 23 ± 4 years: body mass 86 ± 6 kg) volunteered to participate in the study. Each subject attended the laboratory on three occasions, firstly to determine three repetition maximum (3-RM) isotonic strength in the back squat and perform a familiarisation of the experimental task. On the second/third visits subjects completed the hypertrophic training session (HTS) which consisted of six sets of 10 repetitions of 70% of a predicted 1 RM load (kg). Four hours prior to the HTS the subjects consumed 2 ml#x2219;kg-1 total body mass of either the placebo mixture or AOX supplement in a randomised order. Work completed during the strength training session was completed with equipment that had an integrated linear force transducer (Gymaware system, Kinetic Performance Technology, Canberra, Australia). During the placebo trials concentric mean power significantly (p?<?0.05) decreased from sets 1-6. Accumulated power output during the AOX HTS was 6746 ± 5.9 W which was significantly greater compared to the placebo HTS of 6493 ± 17.1 W (p?<?0.05, ES`r?=?0.99). Plasma growth hormone (GH) concentration was significantly less immediately following AOX supplementation (6.65 ± 1.84 vs 16.08 ± 2.78 ml #x2219;ml-1; p < 0.05, ES`r = 0.89). This study demonstrates ingestion of an AOX cocktail prior to a single bout of resistance training improved muscle contractile performance and modulated the GH response following completion of the resistance exercise. Future studies should explore the mechanisms associated with the performance modification and specific muscle adaptations to AOX supplementation in conjunction with heavy RT.